2012
DOI: 10.1002/humu.22215
|View full text |Cite
|
Sign up to set email alerts
|

Description of a Large Family with Autosomal Dominant Hypercholesterolemia Associated with theAPOEp.Leu167del Mutation

Abstract: Apo E mutants are associated with type III hyperlipoproteinemia characterized by high cholesterol and triglycerides levels. Autosomal Dominant Hypercholesterolemia (ADH), due to mutations in the LDLR, APOB or PCSK9 genes, is characterized by an isolated elevation of cholesterol due to high levels of low-density lipoproteins (LDL). We now report an exceptionally large family including 14 members with ADH. Through genome wide mapping, analysis of regional/functional candidate genes and whole exome sequencing, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
4
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 27 publications
3
92
4
2
Order By: Relevance
“…This APOE variant was predicted to have a destabilizing effect on the protein structure here, and this has been confi rmed experimentally recently for the E4 isoform ( 40 ); our patient carried precisely the E4 isoform (patient #3). The p.(Leu167del) found in patient #2 was previously described in ADH patients ( 4,5 ), and our in silico structural analyses suggest that this apoE variant will have impaired LDLR binding properties. The binding defect of p.(Leu167del) was, however, not demonstrated ( 4 ).…”
Section: Discussionsupporting
confidence: 75%
“…This APOE variant was predicted to have a destabilizing effect on the protein structure here, and this has been confi rmed experimentally recently for the E4 isoform ( 40 ); our patient carried precisely the E4 isoform (patient #3). The p.(Leu167del) found in patient #2 was previously described in ADH patients ( 4,5 ), and our in silico structural analyses suggest that this apoE variant will have impaired LDLR binding properties. The binding defect of p.(Leu167del) was, however, not demonstrated ( 4 ).…”
Section: Discussionsupporting
confidence: 75%
“…The decrease in HDL cholesterol (HDL-C) in pcsk9 Ϫ / Ϫ mice has been attributed to the binding of ApoE containing HDL to the upregulated LDLR ( 11 ). Even with a functional LDLR and ApoB, mutations in APOE in humans can lead to hypercholesterolemia (43)(44)(45)(46). To date the role of ApoE in the lipid lowering and athero-protective effects of PCSK9 inhibition is unclear.…”
Section: In Vivomentioning
confidence: 99%
“…We found only one patient heterozygous for a known apoE variant [p.(Leu167del)], considered the cause of FH with dominant transmission [3]. Recently a large study conducted in 228 Spanish FH patients in whom the LDLR, APOB and PCSK9 pathogenic variants had been excluded, showed that nine patients (3.1%) were carriers of the p.(Leu167del) variant [20].…”
Section: Discussionmentioning
confidence: 91%
“…Gain-of-function (GOF) mutations of PCSK9 causing FH are exceedingly rare [6]. Only a single mutation in APOE gene [p.(Leu167del)] was found to be the cause of a dominant FH phenotype [3]. FH-like phenotypes with a recessive transmission are extremely rare.…”
Section: Introductionmentioning
confidence: 99%